Private Kindergarten Teachers' Intention to Remain: A Comparison Between the Effects of Organizational and Individual Psychological Factors - Shi, Song; Zhang, Zizai; Wu, Hotang; Zhang, Xiaomei (Frontiers in Psychology, 2022)
The purpose of this study was 2-fold: to validate the Private Kindergarten Teachers' Intention of Remaining (PKTIR) Questionnaire and the Factors of Teachers' Intention of Remaining (FTIR) Questionnaire, and to comparative study to explore the effects of organizational and individual psychological factors in China. A total of 22 experts were recruited to modify and validate both questionnaires. The results showed that both questionnaires had instruments that are reliable and valid. Then, a total of 582 kindergarten teachers were recruited to explore the comparison between the effects of organizational and individual psychological factors. The results from the structural equation model suggested that the influence of individual psychological factors on kindergarten teachers' intention of remaining was greater compared to the organizational factors. Second, among all the factors, the most explanatory are work connections, sense of work gained from it, satisfaction with the salary, and work discard. To our knowledge, this is the first comparative study to explore the effects of organizational and individual psychological factors in China.